Implementasi Pelatihan Dasar Pengoperasian Komputer untuk Meningkatkan Mutu Pembelajaran - Ayu Setyowati; Gina Maulida; Nur Aini; Nila Fatika Suri; Marlina Putri; Sabrina Aulia Zahra; Nadia Nadia (Jurnal Pengabdian Inovasi Masyarakat Indonesia, 2023)
This computer training activity is carried out with a purpose to provide an understanding of the importance of technology, as well as provide training to improve basic computer operating skills and the use of fundamental computer applications, such as Paint, Microsoft Office Word to grade 5 students of SD Negeri 02 Penusupan. The method of implementing this activity is carried out using the lecture and discussion method between students and presenters, as well as giving practicum related to how to use computers to test students' understanding of the material that has been previously presented. The result of this activity is an increase in students' understanding of basic computer operations and students' skills in using fundamental computer applications, including the use of the Microsoft Office Word application for document creation.